2021
DOI: 10.1097/gme.0000000000001746
|View full text |Cite
|
Sign up to set email alerts
|

Resumed ovarian function and pregnancy in early menopausal women by whole dimension subcortical ovarian administration of platelet-rich plasma and gonadotropins

Abstract: Objective: This study was designed to investigate if whole dimension subcortical ovarian administration of platelet-rich plasma with gonadotropin, in proximity to most ovarian follicles, is effective in restoring ovarian functions in women during early menopause. Methods: Platelet-rich plasma, prepared from 40 mL of autologous peripheral blood using the buffy coat method, was injected into extended subcortical area of bilateral ovaries along with recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In the era of increasing demand for more efficient ovarian stimulation, as many advanced aged women and more women of poor ovarian reserve request IVF treatments, different administration modes of recombinant human FSH (rhFSH) might provide each patient an individualized tailored scheme to optimize the response of COS. Our recent studies proved that rhFSH can be administered intradermally and effectively absorbed and delivered to the ovaries to enhance the follicle growth [ 23 , 24 ]. The rhFSH in combination with platelet rich plasma has recently been directly injected into the target ovarian tissue and ovarian subcortical area to restore the ovarian function and achieve clinical pregnancy in women of premature ovarian insufficiency and early menopause [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the era of increasing demand for more efficient ovarian stimulation, as many advanced aged women and more women of poor ovarian reserve request IVF treatments, different administration modes of recombinant human FSH (rhFSH) might provide each patient an individualized tailored scheme to optimize the response of COS. Our recent studies proved that rhFSH can be administered intradermally and effectively absorbed and delivered to the ovaries to enhance the follicle growth [ 23 , 24 ]. The rhFSH in combination with platelet rich plasma has recently been directly injected into the target ovarian tissue and ovarian subcortical area to restore the ovarian function and achieve clinical pregnancy in women of premature ovarian insufficiency and early menopause [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies show that serum FSH dramatically decreases after ovarian tissue transplantation, inducing the resumption of folliculogenesis in grafts 47,48 , thus possibly delaying the onset of menopause and associated neuropathological changes. Finally, the administration of plateletrich plasma with recombinant FSH to the ovaries was shown to restore ovarian function, at least temporarily, in early post-menopausal women 49 . While this technique is aimed at prolonging a woman's fertility period 49 , it may also hold promise for prevention of menopause-associated AD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the administration of plateletrich plasma with recombinant FSH to the ovaries was shown to restore ovarian function, at least temporarily, in early post-menopausal women 49 . While this technique is aimed at prolonging a woman's fertility period 49 , it may also hold promise for prevention of menopause-associated AD risk.…”
Section: Discussionmentioning
confidence: 99%
“…In the era of increasing demand for more women, many with advanced age, with DOR/IOF request IVF treatments, different administration modes of rhFSH might optimize their response to COS. Our recent studies by administrating rhFSH in combination with PRP directly into the target ovarian tissue and also whole dimension subcortical ovarian administration indicated the restoration of ovarian function and clinical pregnancy in women with premature ovarian insufficiency and early menopause [ 15 , 16 ]. We have also demonstrated that both intradermally and intravaginally administered rhFSH can be absorbed efficiently and enhance ovarian follicle growth in POR women [ 17 , 19 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy of luteal-phase DuoStim in patients with DOR/IOF has not yet been examined. The enhancement of folliculogenesis has recently been shown in women with POI and early menopausal women who received intraovarian administration of rhFSH with platelet-rich plasma (PRP) [ 15 , 16 ]. We, therefore, hypothesized that more oocytes could be obtained by continuing ovarian stimulation after the first oocyte retrieval under direct ovarian administration of rhFSH.…”
Section: Introductionmentioning
confidence: 99%